IMPLEMENTASI MODEL GAME BASED LEARNING MELALUI PERMAINAN MBG UNTUK MENINGKATKAN HASIL BELAJAR MATERI OPERASI HITUNG PECAHAN KELAS V SDIT ABFA - Femmy Indah Septiani; Sri Irawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT Learning fraction addition and subtraction is often a challenge for elementary school students due to its abstract nature, resulting in low learning activity and outcomes. This study aims to describe the improvement of learning activity, student response, and learning outcomes of fifth-grade students at SDIT ABFA Pamekasan through the implementation of the Game Based Learning (GBL) model using the Makanan Bersoal Gratis (MBG) game. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of two meetings, with 23 students as subjects. Data were collected through student activity observation sheets, learning achievement tests, and student response questionnaires, then analyzed using descriptive quantitative analysis. The results showed an improvement in all three measured aspects. The average learning activity score increased from 2.54 (good category) in cycle I to 3.40 (good category) in cycle II. Classical learning completeness increased from 56.5% to 87.0%, with the class average score rising from 75.2 to 83.9. Positive student response increased from 77.6% to 89.5%. Based on these findings, it can be concluded that the implementation of the GBL model through the MBG game is effective in improving students' activity, response, and learning outcomes in fraction operations, making it a viable innovative alternative for elementary mathematics learning.